2020
DOI: 10.21608/ijma.2020.42597.1166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histopathological Changes Between Primary Versus recurrent Rhinosinusitis With Nasal Polyposis

Abstract: Background: Chronic rhinosinusitis associated with nasal polypi [CRSwNP] is one of the two major chronic rhinosinusitis phenotypes. The histopathological changes of such condition may differ between primary and chronic types. Aim of the work:To differentiate between primary and chronic rhinosinusitis with polypi through detection of the histopathological changes of nasal mucosa. Patients and Methods: Eighty-five patients with CRSwNP scheduled for functional endoscopic sinus surgery [FESS] were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For example, a revision FESS CRSwNP control group would enable exploration of whether this population exhibited similar step‐wise improvement with dose escalation. Past studies have shown that patients with revision, relative to primary, FESS CRSwNP demonstrate enhanced fibrosis on histopathology of sinonasal mucosa 9 . Perhaps tissue modification from previous surgical manipulation makes remaining sinonasal tissue less amenable to improvement with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a revision FESS CRSwNP control group would enable exploration of whether this population exhibited similar step‐wise improvement with dose escalation. Past studies have shown that patients with revision, relative to primary, FESS CRSwNP demonstrate enhanced fibrosis on histopathology of sinonasal mucosa 9 . Perhaps tissue modification from previous surgical manipulation makes remaining sinonasal tissue less amenable to improvement with topical corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that patients with revision, relative to primary, FESS CRSwNP demonstrate enhanced fibrosis on histopathology of sinonasal mucosa. 9 Perhaps tissue modification from previous surgical manipulation makes remaining sinonasal tissue less amenable to improvement with topical corticosteroids. This possibility underscores the importance of individualized medical management of the patient with post-FESS CRSwNP.…”
Section: Discussionmentioning
confidence: 99%